Analysis of Original Japanese ‘Uchisoto’ Concept Used by Indonesian Speaker as Tourism Actors in Bali - Anak Agung Ayu Dian Andriyani; Djatmika Djatmika; Sumarlam Sumarlam; Ely Triasih Rahayu (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This study aimed to analyze the implementation of uchi ‘ingrup’ soto‘outgrup’ from dialogue between tourism actors and Japanese tourists in Bali. The research site was characterized by formal situation at one of the largest Japanese travel agencies in Bali and by non-formal situations carried out in the Kuta beach in Badung regency. This case study grappled with linguistic data in the form of dialogues between tourism actors and Japanese tourists that was laden with the Uchisoto concept. The data collection technique included recording techniques, reference and record techniques, and in-depth interview techniques with 25 tourism actors in an unstructured way to get data in their natural contexts. The data transcribed were classified according to the context of the speech situation and then analyzed using domain, taxonomy, compound and cultural analysis. The research results highlighted the errors in implementing the Uchisoto concept because of differences in mindset and culture, within both formal and non-formal situations. This is evident from the level of speech markers used which still respect the leaders in front of customers. Despite these mistakes, tourism actors are able to carry out maximum hospitality so Japanese tourists understand this condition. They understand the different concepts of thinking and minimum understanding of these tourism actors. These findings help tourism actors in the Japanese business to use the Uchisoto concept when communicating with Japanese tourists and for tour guides, travel agencies and also language schools to provide trainings related to Japanese language and business culture.